Penggunaan Metode Bernyanyi dalam Menghafal Mufrodat (Kosakata) Bahasa Arab di MI - Ali Imron; Dewi Farda Fajriyah (Dawuh Guru: Jurnal Pendidikan MI/SD, 2021)
This article aims to determine the effect of the singing method on the ability to memorize mufrodats (vocabulary) in MI Baitul Huda. This research is a quantitative research with data collection techniques in the form of written tests, questionnaires, interviews, observation and documentation. The data collection analysis used statistical analysis. Based on the results of the questionnaire answered by 22 respondents, it shows a mean with a value of 72 indicating an increase in the ability to memorize mufrodat al-fawaakih material for the experimental class students using the singing method with an average value of 90.90 while the control class with the conventional method obtained an average of 66 90. The effect of the use of the singing method on the ability to memorize mufrodates from the results of the hypothesis test can be seen that the r-count is 0.582, while the r-table is at a significant level of 1% = 0.537 and 5% = 0.423. The significance level of 1% r-count (0.582)> from the r-table (0.537), while the significant level of 5% r-count (0.582)> from the r-table (0.423). So it can be ascertained that there is a significant effect of using the singing method on the ability to memorize mufrodats.